2021
DOI: 10.3389/fmicb.2021.638047
|View full text |Cite
|
Sign up to set email alerts
|

Lipoarabinomannan as a Point-of-Care Assay for Diagnosis of Tuberculosis: How Far Are We to Use It?

Abstract: Tuberculosis (TB) is still a severe public health problem; the current diagnostic tests have limitations that delay treatment onset. Lipoarabinomannan (LAM) is a glycolipid that is a component of the cell wall of the bacillus Mycobacterium tuberculosis, the etiologic agent of TB. This glycolipid is excreted as a soluble form in urine. The World Health Organization has established that the design of new TB diagnostic methods is one of the priorities within the EndTB Strategy. LAM has been suggested as a biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 147 publications
(180 reference statements)
0
24
0
2
Order By: Relevance
“…The detection of LAM has been endorsed as a diagnostic tool by WHO, and enzyme-linked immunosorbent assays (ELISA) and lateral flow assays are commercially available ( Whitelaw and Sturm, 2010 ). During M. tuberculosis infection, LAM exists in various body fluids; therefore, it can be an ideal candidate biomarker for the detection of M. tuberculosis ( Flores et al., 2021 ). In recent years, novel urine-based LAM antigen detection technology has been developed, including the Fujifilm SILVAMP TB LAM (Fuji LAM) test and the Alere Determine TB LAM Ag (Alere LAM) test ( Bulterys et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of LAM has been endorsed as a diagnostic tool by WHO, and enzyme-linked immunosorbent assays (ELISA) and lateral flow assays are commercially available ( Whitelaw and Sturm, 2010 ). During M. tuberculosis infection, LAM exists in various body fluids; therefore, it can be an ideal candidate biomarker for the detection of M. tuberculosis ( Flores et al., 2021 ). In recent years, novel urine-based LAM antigen detection technology has been developed, including the Fujifilm SILVAMP TB LAM (Fuji LAM) test and the Alere Determine TB LAM Ag (Alere LAM) test ( Bulterys et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipoarabinomannan (LAM) is a specific component of the cell envelope of M. tuberculosis ( 7 ). During M. tuberculosis infection, LAM exists in a variety of body fluids; therefore, it can be an ideal candidate biomarker for detecting M. tuberculosis ( 8 ). More meaningfully, Nathavitharana et al found that using lateral flow lipoarabinomannan assay (LF-LAM) as part of a TB diagnostic testing strategy likely reduced mortality and probably resulted in a slight increase in anti-tuberculosis therapy initiation in HIV patients ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsputum based tests are required in particular for diagnosis of EPTB, people living with HIV and in children. The next-generation lipoarabinomannan (LAM) test are showing improved performance over original LAM tests [7,8], but don’t detect TB drug resistance. WHO guidelines on TB diagnosis, updated in 2021, summarize the current evidence and recommendations on TB diagnosis [9].…”
Section: Diagnosis Of Mycobacterium Tuberculosis Drug Resistancementioning
confidence: 99%